Malaysian women’s intention to purchase green cosmetic products/ Normaziah Che Musa, Muhammad Syafiq Mohd Salleh, Khaw Thean Boon, Azri Ab Aziz, Christyne Tyller, Tan Chun Liang and Wong Wan Jee - Che Musa, Normaziah; Mohd Salleh, Muhammad Syafiq; Khaw, Thean Boon; Azri, Ab Aziz; Tyller, Christyne; Tan, Chun Liang; Wong, Wan Jee (UiTM Cawangan Johor, 2023)
Understanding consumer purchase intention is crucial for the sustainable success of cosmetic companies. The Theory of Planned Behaviour (TPB) has been used as the underpinning theory for this study. This study collected samples from 300 female respondents via a questionnaire of 46 questions. The result of the data analysis was able to show that all four components; personal norms, attitude, environmental concern, and willingness to pay, have a positive relationship with the purchase intention of green cosmetic products. The outcome of this study contributed to the enrichment of the underpinning the on. It has provided useful marketing insights for cosmetic manufacturers, and it promotes social awareness to protect our environment for future generations. Keywords: Theory of Planned Behaviour, Personal Norms, Attitude, Environmental Concern, Willingness to Pay, Purchase Intention